2015
DOI: 10.1159/000440628
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-Occluded Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma: A Single-Center Experience

Abstract: Objective: To investigate whether balloon-occluded transcatheter arterial chemoembolization (b-TACE) can produce a more dense accumulation of iodized oil in various stages of hepatocellular carcinoma (HCC), from single to uncountable, to overcome inferior local control. Materials and Methods: We studied 27 patients with HCC, including single to uncountable multiple lesions, who underwent b-TACE between August 2013 and April 2015. Dynamic CT was performed at baseline and 1-3 months after b-TACE. The treatment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
2
21
2
Order By: Relevance
“…Although TACE is regarded as an alternative therapy of surgical resection for advanced HCCs, it didn't seem to prolong PFS or OS as shown in our study. A recent relevant study [48] also suggested that TACE didn't improve the efficacy of treatment for advanced HCCs, and therefore it was not recommended for use in combination with other therapies [49]. In our study, we found that patients who underwent hepatecotomy with or without liver transplantation tended to have a better OS ( p = 0.006).…”
Section: Discussionmentioning
confidence: 51%
“…Although TACE is regarded as an alternative therapy of surgical resection for advanced HCCs, it didn't seem to prolong PFS or OS as shown in our study. A recent relevant study [48] also suggested that TACE didn't improve the efficacy of treatment for advanced HCCs, and therefore it was not recommended for use in combination with other therapies [49]. In our study, we found that patients who underwent hepatecotomy with or without liver transplantation tended to have a better OS ( p = 0.006).…”
Section: Discussionmentioning
confidence: 51%
“…First, even though results of imaging findings were matched to the Japanese definition of TACErefractory, clinicians judged the therapeutic response as SD. It is also possible that some clinicians want to re-try TACE by changing chemo-agents, embolization particles, or catheter devices, such as beads [30,31] or a balloon catheter [32,33] . Even after excluding patients who no longer continued with TACE because of worsening hepatic function or progression of HCC, the present findings showed that repeated TACE procedures made hepatic function worse at a fixed frequency, while the deviation rate for worsened grade according to an increased number of TACE procedures was larger when patients were assessed using ALBI-grade rather than Child-Pugh classification.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the establishment of a nationwide HCC surveillance program contributed to improved overall survival (OS) rates [2] . With respect to treatment, sorafenib is effective for cases of advanced HCC [3,4] , and various embolic materials and catheters have been developed for transarterial chemoembolization (TACE) [5] . These advances have contributed to improved OS rates in the past decade.…”
Section: Introductionmentioning
confidence: 99%